If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 = -5 + 6x + -1(4x + 3) Reorder the terms: -3 + 7x = -5 + 6x + -1(4x + 3) Reorder the terms: -3 + 7x = -5 + 6x + -1(3 + 4x) -3 + 7x = -5 + 6x + (3 * -1 + 4x * -1) -3 + 7x = -5 + 6x + (-3 + -4x) Reorder the terms: -3 + 7x = -5 + -3 + 6x + -4x Combine like terms: -5 + -3 = -8 -3 + 7x = -8 + 6x + -4x Combine like terms: 6x + -4x = 2x -3 + 7x = -8 + 2x Solving -3 + 7x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 7x + -2x = -8 + 2x + -2x Combine like terms: 7x + -2x = 5x -3 + 5x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 5x = -8 + 0 -3 + 5x = -8 Add '3' to each side of the equation. -3 + 3 + 5x = -8 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = -8 + 3 5x = -8 + 3 Combine like terms: -8 + 3 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| x^3-2=0 | | 10-8x=27-15x | | -x+11=5x+12-(7x-2) | | S^2-2s-8=0 | | 6x^2+4=10 | | 81-2(x-1)2=51 | | 3x^2-4=4-3x^2 | | -12x-9x=9x+24 | | 2x+5-15+3x=5 | | 6x(5x+3)=18x | | 5k-12=20 | | 2x+4(2x+4)=50 | | 8x-8=3x+4 | | 6x+80=9x-7 | | 12-7x=162-42x | | 129-9x=9x+15 | | 2*x*x+5=10 | | 9+.44444444444=19 | | 6x+83=9x-7 | | 2x^3-x^2-1=0 | | 2+45-3/2=12b | | 8t-5=19 | | 6x-11-7x+12= | | 4x^2-4x+4=0 | | -x^2+x-12=0 | | 4(y+3)=7-5y | | (19x-17)-(3x-72)=-13+(13x+83) | | 9-9x=84-44x | | (1x)(6x)+7x+12=0 | | 6x+2=5(x+1) | | 80-2x=4x-14 | | (6x)(6x)+7x+12=0 |